Total synthesis of (±)-vinoxine: construction of the bridged pyrido[1, 2-a]indole skeleton via Tf2O-mediated Bischler–Napieralski reaction and stereoselective radical cyclization. Issue 30 (8th March 2022) - Okada, Kosuke; Ueda, Hirofumi; Tokuyama, Hidetoshi
Abstract : The total synthesis of (±)-vinoxine was achieved featuring the assembly of a substituted tetrahydropyrido[1, 2- a ]indole skeleton through the Tf2 O-mediated Bischler–Napieralski reaction. Abstract : The total synthesis of (±)-vinoxine was achieved featuring the assembly of a multi-substituted tetrahydropyrido[1, 2- a ]indole skeleton through the Tf2 O-mediated Bischler–Napieralski reaction. The characteristic diazabicyclo[3.3.1]nonane skeleton was stereoselectively constructed via radical cyclization based on the one stereochemistry of the C3 position. The established methodology provides new options for the synthesis of natural products and pharmaceuticals containing the multi-substituted pyrido[1, 2- a ]indole skeleton.